Socioeconomic Disparities in Referral for Invasive Hemodynamic Evaluation for Advanced Heart Failure: A Nationwide Cohort Study. (31st August 2021) - Larsson, Johan; Kristensen, Søren L.; Madelaire, Christian; Schou, Morten; Rossing, Kasper; Boesgaard, Søren; Køber, Lars; Gustafsson, Finn
Abstract : Background: Factors determining referral for advanced heart failure (HF) evaluation are poorly studied. We studied the influence of socioeconomic aspects on the referral process in Denmark, which has a taxpayer-funded national health care system. Methods: We identified all patients aged 18 to 75 years with a first diagnosis of HF during 2010 to 2018. Hospitalized patients had to be discharged alive and were then followed for the outcome of undergoing a right heart catheterization (RHC) used as a surrogate marker of advanced HF work-up. Results: Of 36 637 newly diagnosed patients with HF, 680 (1.9%) underwent RHC during the follow-up period (median time to RHC of 280 days [interquartile range, 73–914]). Factors associated with a higher likelihood of RHC included the highest versus lowest household income quartile (HR, 1.56 [95% CI, 1.18–2.05]; P =0.002), being diagnosed with HF at a tertiary versus nontertiary hospital (HR, 2.19 [95% CI, 1.84–2.61]; P <0.001) and during a hospitalization versus outpatient visit (HR, 1.65 [95% CI, 1.41–1.93]; P <0.001). Level of education, and occupational status were not independently associated with RHC. Older age, cancer, and a psychiatric diagnosis were independently associated with a decreased probability of RHC. Conclusions: Higher household income, HF diagnosis during hospitalization, and first admission at a tertiary hospital were associated with increased likelihood of subsequent referral for RHC independent of other demographic and clinical variables. Greater attention may be required to ensure timely referral for advanced HF therapies in lower income groups.